2010
DOI: 10.1002/pssc.200982651
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of photoluminescence spectra at the bioconjugation of core‐shell CdSe/ZnS quantum dots

Abstract: The photoluminescence (PL) of nonconjugated and bioconjugated core‐shell CdSe/ZnS quantum dots (QDs) has been discussed in this paper. Commercial CdSe/ZnS QDs with the size of 3.6‐4.0 nm covered by polymer with emission at 560‐565 nm (2.19‐2.22 eV) have been used. The QD bioconjugation is performed with the mouse anti PSA (Prostate‐Specific Antigen) antibody (mab). PL spectra of nonconjugated QDs are characterized by a superposition of PL bands related to exciton emission in the CdSe core (2.19‐2.22 eV) and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…We have shown early (Torchynska et al, 2009 a, b and c) that core/shell CdSe/ZnS QDs with radiative interface state are very promising for the spectroscopic confirmation of the bioconjugation process. These systems permit to detect both the variation of PL intensity at the bioconjugation, that ordinary has been monitored, and the transformation of emission spectra related to the change of a full width at half maximum (FWHM) (Torchynska b and c;Vega Macotela et al, 2010a) and PL peak positions, as well as the transformation of Raman scattering spectra (Torchynska et al, 2007;Torchynska et al, 2008;Vega Macotela, 2010b;. The nature of radiative interface states in the core /shell CdSe/ZnS QDs has to be investigated.…”
Section: Pl Spectra Of Nonconjugated Core/shell Cdse/zns Qds With Intmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown early (Torchynska et al, 2009 a, b and c) that core/shell CdSe/ZnS QDs with radiative interface state are very promising for the spectroscopic confirmation of the bioconjugation process. These systems permit to detect both the variation of PL intensity at the bioconjugation, that ordinary has been monitored, and the transformation of emission spectra related to the change of a full width at half maximum (FWHM) (Torchynska b and c;Vega Macotela et al, 2010a) and PL peak positions, as well as the transformation of Raman scattering spectra (Torchynska et al, 2007;Torchynska et al, 2008;Vega Macotela, 2010b;. The nature of radiative interface states in the core /shell CdSe/ZnS QDs has to be investigated.…”
Section: Pl Spectra Of Nonconjugated Core/shell Cdse/zns Qds With Intmentioning
confidence: 99%
“…Other parts of CdSe/ZnS QDs (named 525N, 565N, 605N and 640N) have been left nonconjugated and serve as a reference object. Nonconjugated CdSe/ZnS QDs in the form of a 5 mm size spot were dried on a polished surface of crystalline Si substrates as described earlier in (Torchynska et al, 2009 a, b and c;Vega Macotela et al, 2010a). PL spectra were measured at 300 K and some of them at 10 K at the excitation by a He-Cd laser with a wavelength of 325 nm and a beam power of 20 mW using a PL setup described in (Torchynska et al, 2009 a, b and c;Vega Macotela et al, 2010a).…”
Section: Pl Spectra Of Nonconjugated Core/shell Cdse/zns Qds With Intmentioning
confidence: 99%
See 1 more Smart Citation
“…These kits contain aminederivatized polymer-coated QDs and the amine-thiol cross-linker SMCC. The samples of QDs (bioconjugated and nonconjugated) in the form of a 5-mm spot were dried on a surface of crystalline Si substrates (Figure 1) as described earlier by Torchynska [22] and Vega Macotela et al [24].…”
Section: Qd Bioconjugation Process and Experimental Detailsmentioning
confidence: 99%
“…A set of publications, related to the study of QD bioconjugation using PL spectroscopy, revealed that the emission intensity of QDs decreased [12,24,25] or increased [22,26] owing to the energy exchange between the QDs and the biomolecules. Thus, the QD luminescence intensity depends on the concentration of attached biomolecules, promising the QD application as a protein sensor as well [6].…”
Section: Introductionmentioning
confidence: 99%